Exploring the mechanisms of yoga-based cardiac rehabilitation in heart failure via assessment of endothelial function, genomics and arterial health (Yoga-EndOmics): a study protocol - Shetty, Vindya Vasu; Patil, Laxmi Ramchandra; Patil, Satish G.; Aithal, Kiran; Oli, Ajay Kumar; Yenagi, Vijay Aravind; Kaulgud, Ram S.; Dharne, Mahesh; Chandra Sekaran, Ambalam M.; Prabhakaran, Dorairaj (BMJ Open, 2026)
Introduction Heart failure (HF) remains a major global health challenge, particularly in low-resource settings where access to comprehensive cardiac rehabilitation (CR) is limited. Yoga, a culturally contextualised mind-body intervention, holds promise as an adjunctive therapy in CR. The Yoga-EndOmics study aims to evaluate the effects of Yoga-based cardiac rehabilitation (Yoga-CaRe) on gene expression, endothelial function, vascular biomarkers and clinical outcomes in systolic HF, providing mechanistic insights into its potential integration into conventional cardiac rehabilitation.Methods and analysis This is a prospective, randomised, open-label, blinded-endpoint (PROBE) mechanistic trial enrolling 78 patients with HF with reduced ejection fraction (HFrEF). Participants will be randomised in a 1:1 ratio to receive either a structured Yoga-CaRe intervention or enhanced standard care for 3 months. The Yoga-CaRe group will attend 20 supervised sessions with guided home practice involving tailored asanas, pranayama and meditation. Primary outcomes are changes in endothelial-dependent flow-mediated dilation (FMD) and functional exercise capacity at 3 months. Secondary outcomes include changes in arterial compliance and stiffness, circulating biomarkers of endothelial dysfunction, oxidative stress and inflammation, and immediate changes in global gene expression profiles in peripheral blood mononuclear cells following the Yoga-CaRe intervention. Data will be analysed using analysis of covariance (ANCOVA) for between-group comparisons and significant analysis of microarray (SAM) for global gene expression profiles.Ethics and dissemination The study has received ethical clearance from the Institutional Ethics Committee of the SDM College of Medical Sciences and Hospital, India (SDMIEC/2025/1072) and is registered with the Clinical Trials Registry of India. Findings will be disseminated through peer-reviewed journals, scientific conferences and stakeholder engagement platforms to inform future integrative strategies in HF management.Trial registration number CTRI/2023/12/060758
Keywords: DNA Methylation; Genetics; Heart failure; Molecular Biology; Randomized Controlled Trial